Application Of A High-Intensity Cooling System To DC-Arc Furnace Production Of Ferrocobalt At Chambishi - L. R. Nelson (The Southern African Institute of Mining and Metallurgy, 2004)
A review is presented of the furnace cooling system design and operating developments since the initial furnace start-up in January 2001 of the Chambishi DC-arc furnace to produce ferrocobalt alloy. The furnace operating conditions present a number of challenges to the furnace designers and operators, in particular, to provide a sustainable lining that can withstand the highly corrosive siliceous slag (roughly 50% SiO2). This is exacerbated by the dual requirement of operating this slag in a relatively highly superheated state (?T ?400°C when tapped at 1550°C) to ensure that the ferroalloy can be tapped (estimated 1370°C alloy liquidus temperature) prior to atomization. The core design challenge occurs at the alloy-slag interface, where a single refractory type cannot simultaneously meet the dual requirement of both adequate alloy and slag corrosion compatibility. Progression by the fourth furnace campaign to involve a retrofit of the bath sidewall to HATCH high-intensity, water-cooled, copper Waffle coolers and tap blocks is described. This involves operation of the entire slag bath, the slag-alloy interface and a portion of the alloy within a more chemically compatible refractory/slag (and possibly at times even an alloy) freeze-lining. Due to the high furnace power density employed (up to 500 kW/m2 hearth area), coupled with the large slag superheat needed, the resulting imposed peak bath sidewall heat fluxes are substantial, especially in the alloy (typically averaging 170 kW/m2), and on occasion have exceeded 1000 kW/m2. The performance of the HATCH Copper Waffle coolers under such aggressive process pyrometallurgical conditions is described. Aspects of the design and especially operating strategies to effect sustained production at up to 38 MW power input are also discussed.